Tandem Dye-Doped Nanoparticles for NIR Imaging via Cerenkov Resonance Energy Transfer - Genovese, Damiano; Petrizza, Luca; Prodi, Luca; Rampazzo, Enrico; De Sanctis, Francesco; Spinelli, Antonello Enrico; Boschi, Federico; Zaccheroni, Nelsi (Frontiers in Chemistry, 2020)
The detection of the Cerenkov radiation (CR), is an emerging preclinical imaging technique allowing to monitor the in vivo distribution of radionuclides. Among its possible advantages, the most interesting is the simplicity and cost of the required instrumentation compared, for example, to that required for PET scans. On the other hand, one of its main drawbacks is related to the fact that CR, presenting the most intense component in the UV-vis region, has a very low penetration in biological tissues. To address this issue, we present here multifluorophoric silica nanoparticles properly designed to efficiently absorb the CR radiation and to have a quite high fluorescence quantum yield (0.12) at 826 nm. Thanks to a highly efficient series of energy transfer processes, each nanoparticle can convert part of the CR into NIR light, increasing their detection even under 1.0 cm thickness of muscle.